OECS Energy Issues and Options - Hertzmark, Donald (World Bank, Washington, DC, 2014)
This study evaluates the current energy situation in the member states of the Organization of Eastern Caribbean States (OECS) and identifies selected investment options and policy issues for new energy projects. The emphasis of the study is on large energy systems and ways to link one of more of the OECS countries. Complementary smaller-scale systems, in the form of wind, are also considered. This study is not an exhaustive survey either of each OECS member country or of all possible energy technologies for the OECS countries. Rather, it is intended to address the key energy-economy interaction in the electricity sector and to assess potential new supply investments. A key issue is how to bring some of the benefits of larger scale, more efficient power generation technology to these small island systems. The report begins with a summary of recommendations and findings for OECS policies and actions. Part 1 contains an assessment of the energy sector with two main components, a review of recent studies on energy in the OECS, and a summary of current use of fuel and energy, primarily electricity in the OECS member states. Part 2 starts with a review of international experiences in island energy systems, including integration efforts. Based on the review of previous work, ongoing efforts in the region and the energy needs of the OECS members, several options are discussed in Chapter 5 for both large and small-scale investments. These include (1) inter-island gas pipeline; (2) Liquefied natural gas/compressed natural gas supply; (3) geothermal development with cable links to other islands; and (4) wind farms, linked to multi-island power systems. Chapter 6 highlights the costs associated with various options, and Chapter 7 shows the economic and financial aspects of the various options, as well as their compatibility with policy objectives extracted from OECS member country energy strategy documents.